2000
DOI: 10.1021/ja9930364
|View full text |Cite
|
Sign up to set email alerts
|

Thiazole and Thiophene Analogues of Donor−Acceptor Stilbenes:  Molecular Hyperpolarizabilities and Structure−Property Relationships

Abstract: We calculate the first hyperpolarizability (β) of several thiazole and thiophene analogues of donoracceptor stilbene compounds using the ZINDO (sum-over-states) formalism. Because of the inherent dipolar nature of thiazole, in which C2 is electron-poor and C5 is electron-rich, the relative orientation of the thiazole subunit in the dipolar chromophore dramatically affects the nonlinear optical properties. In the "mismatched" case, the dipole of the thiazole ring opposes the molecular dipole created by the dono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
194
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 332 publications
(206 citation statements)
references
References 48 publications
12
194
0
Order By: Relevance
“…It is interesting to compare our results with those obtained for well-known conjugated organic molecules, which are characterized by 2-dimensional instead of 3-dimensional electronic delocalization. Assuming that the planar geometry for donor/acceptor-substituted heterocyclic is analogous to stilbene, conformers with di®erent cis/trans molecular moieties orientations were considered, and it has been shown that both energy and the hyperpolarizability do not change signi¯cantly [9]. The situation with regard to 6-vertex carboranes is more complicated.…”
Section: -31mentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting to compare our results with those obtained for well-known conjugated organic molecules, which are characterized by 2-dimensional instead of 3-dimensional electronic delocalization. Assuming that the planar geometry for donor/acceptor-substituted heterocyclic is analogous to stilbene, conformers with di®erent cis/trans molecular moieties orientations were considered, and it has been shown that both energy and the hyperpolarizability do not change signi¯cantly [9]. The situation with regard to 6-vertex carboranes is more complicated.…”
Section: -31mentioning
confidence: 99%
“…Hyperpolarizability is usually associated with an extended º -conjugated system, capped with donor and acceptor substituents. The e±ciency of the º -bridge as a pathway for charge transfer between donor and acceptor groups has been the subject of extensive theoretical and experimen-tal studies [4], [5], [6], [7], [8], [9]. A variety of º -conjugated moieties, namely polyene and polyyne chains, aromatic cycles such as benzene, pyridine, thiophene and other heterocycles, as well as their combinations, have been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…In the past years, considerable efforts focused on the development of organic materials with large molecular hyperpolarizabilities, improved optical transparency, etc. [5] [6]. For a material having useful and highly efficient nonlinear optical properties, the constituting molecules need first to exhibit large molecular hyperpolarizabilities, which are generally characterized by a highly extended π-conjugated chain with electron donor-acceptor pair at the ends (D-π-A).…”
Section: Introductionmentioning
confidence: 99%
“…It has been theoretically and experimentally shown that heteroaromatic-based chromophores [11][12][13][14] and multi-dipolar chromophores [15][16][17][18] have larger macroscopic nonlinearities, higher thermal stability as well as better orientational order and stability compared to those of one-dimensional, donor-acceptor disubstituted π-conjugated molecules. Heterocyclic compounds have lower delocalization energy than that of benzene; they can offer better effective conjugation than that of benzene in donor-acceptor compounds.…”
Section: Introductionmentioning
confidence: 99%